Features of Clinical Phenotypes of Food Allergy Syndrome of Cross-reactivity - T. A. Evdokimova; F. I. Petrovskii; L. M. Ogorodnova; M. M. Fedotova; O. S. Fedorova ("Paediatrician" Publishers LLC, 2013)
In recent years a great attention is paid to the study of such an immune phenomenon, as a syndrome of cross-reactivity. It is already proved that often the clinical manifestations of food allergy are not linked to the product of the power supply, but can be caused by pollen of plants. The possibilities of modern diagnostics allow us not only to determine the type of sensitization, but also identify the «guilty» protein allergen-trigger. This article discusses the possible clinical manifestations of food allergy, due to the cross-reactions as between related, and taxonomically not related allergens. The algorithm of forecasting of severity of clinical reactions, as well as a list of proteins, the most often involved in the reactions of intersection is given.